A THREE-PILLAR SYNERGISM REINFORCEMENT MODEL IN JUDICIAL FUNCTION POLICY AT VILLAGE LEVEL - Mukhlis Mukhlis; Safi Safi; Rina Yulianti (UNTAG Law Review, 2017)
The poor people's difficult access to formal judicature system, in fact, has been a national problem, as indicated with previous studies. Although the largescale change of justice access has been made by government through a variety of policies such as justice program for everyone including poor people and marginalized group in Presidential Instruction Number 3 of 2010, mobile justice system, in fact, has not been able to give the way out. This study was a nondoctrinal/ socio legal research law taken place in Madura area. The objective of research was to formulate A Three-Pillar Synergism Reinforcement Model in Judicial Function Policy at Village Level as one of juridical instrument or legal basic argument for formulating and developing policy at village government. The result of research showed that in Madura area, considering inventorying and identification, the legal problem encountered by poor people in village included trading, inheritance, land, debt-loan disputes, drugs, domestic violence, murder, chicken fighting and different faiths. Law Number 6 of 2014 about Village Government, Article 28 obliges the Village Head to resolves a variety disputes occurring in village, it is also supported by Republic of Indonesia Police Head Regulation (Peraturan Kapolri) Number 7 of 2008 about Basic Guideline of People Policing Strategy and Implementation in Organizing Polri's Duty, and furthermore followed up with Telegram Letter of East Java Local Police Head Number: ST/38/I/2014/ DITBINMAS on January 2014 about the optimization of Pre-emptive activity by empowering the three pillars existing at village (bhabinkamtibmas, babinsa, and village head/lurah as well as society leader). Polri Institution's initiative to empower the community in Kamtibmas (society orderliness and security) field should be appreciated, as it will encourage the creation of justice access at village level cheaply, quickly, and simply. This three pillar legitimacy can be formulated in government policy model at village level with the reinforcement through Village Regulation.